English Vocabulary Mastery Profile of STIS Harsy Central Lombok Students - Sudiani, Sudiani (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2024)
This study explores the English vocabulary mastery profile of fifth-semester students in the Family Law Program at STIS Harsy, Central Lombok. The primary objective is to identify students' vocabulary proficiency levels, as vocabulary is a key foundation for productive language skills. Using a descriptive research method, the study evaluates the vocabulary skills of all students within the specified group through a multiple-choice vocabulary mastery test. Results categorize student vocabulary proficiency into three levels: